Frost resistance in alpine woody plants - Neuner, Gilbert (Frontiers in Plant Science, 2014)
This report provides a brief review of key findings related to frost resistance in alpine woody plant species, summarizes data on their frost resistance, highlights the importance of freeze avoidance mechanisms, and indicates areas of future research. Freezing temperatures are possible throughout the whole growing period in the alpine life zone. Frost severity, comprised of both intensity and duration, becomes greater with increasing elevation and, there is also a greater probability, that small statured woody plants, may be insulated by snow cover. Several frost survival mechanisms have evolved in woody alpine plants in response to these environmental conditions. Examples of tolerance to extracellular freezing and freeze dehydration, life cycles that allow species to escape frost, and freeze avoidance mechanisms can all be found. Despite their specific adaption to the alpine environment, frost damage can occur in spring, while all alpine woody plants have a low risk of frost damage in winter. Experimental evidence indicates that premature deacclimation in Pinus cembra in the spring, and a limited ability of many species of alpine woody shrubs to rapidly reacclimate when they lose snow cover, resulting in reduced levels of frost resistance in the spring, may be particularly critical under the projected changes in climate. In this review, frost resistance and specific frost survival mechanisms of different organs (leaves, stems, vegetative and reproductive over-wintering buds, flowers and fruits) and tissues are compared. The seasonal dynamics of frost resistance of leaves of trees, as opposed to woody shrubs, is also discussed. The ability of some tissues and organs to avoid freezing by supercooling, as visualized by high resolution infrared thermography, are also provided. Collectively, the report provides a review of the complex and diverse ways that woody plants survive in the frost dominated environment of the alpine life zone.